Kinerja Karyawan Dalam Meningkatkan Pelayanan Penjualan Sepeda Motor Yamaha - Ariani, Nora Ariani; Juemi, Juemi (Jurnal Metaverse ADPERTISI, 2025)
The purpose of this study was to determine employee performance in improving Yamaha motorcycle sales services at Commanditaire. Vennotschap (CV). Akai Jaya Motor Palu and to determine the inhibiting and supporting factors and alternative solutions. The population in this study were all employees of Commanditaire Vennotschap (CV) Akai Jaya Motor Palu totaling 190 people, while the number of customers and clients was 70 people. The total number was 260 people. To achieve this goal, a sample of 37 people was taken, and for data collection techniques, observation, interviews, questionnaires and documentation were used. While the data analysis technique used was data collected qualitatively, namely describing the variables studied. The technique used in sampling employees of Commanditaire Vennotschap (CV). Akai Jaya Motor Palu is purposive sampling, which is deliberately selecting and determining people who know more about the problem being studied. For consumers or customers who use accidental sampling, anyone who happens to be found by the researcher and is suitable as a data source. The variables that influence (X) are Employee Performance, namely the Ability to carry out and complete daily tasks well and provide optimal service to the community in accordance with procedures. By using the following indicators: Productivity, Service Quality, Responsiveness, Responsibility. Dependent Variable or Variable influenced (Y) namely: Improving Yamaha Motorcycle Sales Services at the Commanditaire Vennotschap (CV) Akai Jaya Motor Palu Branch, in the process of improving services. The results of the study indicate that the quality of service is still not good because employees do not have a strong commitment to service quality. The speed of service is due to several things such as delays in handling customer requests, long response times, or long waiting times in after-sales services. Employee performance when viewed from the productivity indicator is good and responsiveness and responsibility are also good. Employee performance at CV.Akai Jaya Motor Palu when viewed from the Right, Cheap and Friendly Employees indicator is good and in accordance with expectations.